Does ischemia-modified albumin level predict severity of obstructive sleep apnea? - Düger, Mustafa; Seyhan, Ekrem Cengiz; Günlüoğlu, Mehmet Zeki; Bolatkale, Mustafa; Özgül, Mehmet Akif; Turan, Demet; Uğur, Efsun; Ülfer, Gözde (Springer, 2021)
Objective and aim Ischemia-modified albumin (IMA) is a newly recognized marker of chronic inflammation used to evaluate oxidative stress status in patients with various diseases. We explored the possible relationship between IMA levels and obstructive sleep apnea (OSA). Methods In this retrospective study, 169 of 216 sequential patients being evaluated for suspicion of OSAS met inclusion criteria. Polysomnography confirmed OSA in 86 patients (51%) while 81 patients (49%) without OSA were categorized as control subjects. All study participants were tested for blood IMA level, neutrophil/lymphocyte ratio (NLR), C-reactive protein (CRP) level, and red blood cell distribution width (RDW). Results The serum IMA level was significantly higher in patients with OSAS than controls (p = 0.008). The serum IMA level increased significantly as OSAS severity increased (r = 0.50, p < 0.001) and was positively correlated with the AHI (r = 0.41, p < 0.001), CRP level (r = 0.31, p = 0.004), body mass index (r = 0.24, p = 0.022), RDW (r = 0.31, p = 0.03), oxygen desaturation index (ODI) (r = 0.22, p = 0.02), and negatively correlated with the hemoglobin concentration (r = - 0.28, p = 0.04) and minimum hemoglobin oxygen saturation (SpO2) (r = - 0.25, p = 0.02). Receiver operator curve (ROC) analysis showed that the optimal serum IMA, CRP, RDW, and NLR values were not different for predicting OSAS diagnosis (areas under the curves (AUC) = 0.62, 0.59, 0.60, and 0.43, respectively). However, the serum IMA level was superior in reflecting OSAS severity (AUC = 0.78) compared to CRP, RDW, and NLR values (AUC = 0.61, 0.53, and 0.51, respectively) (all p < 0.001). Conclusion Like other markers of inflammation, blood IMA levels were significantly elevated in patients with OSA. However, blood IMA level was a better predictor of disease severity than the other markers.
Keywords: Ischemia-Modified Albumin; Apnea-Hypopnea Index; Obstructive Sleep Apnea Syndrome; Oxidative Stress